La investigación aplicada en la cualificación de la práctica docente (2013)
The changes mark the course of the 21st century, leading to determine the quality as a bellwether for global positioning, regional and local echoing this, education systems consider evidence that diagnostic census half the quality of education, but also provide a comparative resource best education systems, educational institutions, public and private sectors, urban and rural contexts. What determines the quality of the best education systems? , The first factor is the cultural foundation of the family and teacher training as a determining factor. A consolidated teacher training to conduct research from the field of performance the classroom. In correspondence with the above stated, the article initially refers to the best education systems according to the PISA results, what are the selection criterion to the teaching profession, at once considered the UNESCO document (2012 ) "Background and criterion for the development educational politics in Latin America and the Caribbean" to show some features of teacher education and critical aspects in the national context continues taking as the source document MEN (2012 ) "Politics and Colombian system of training and professional development." A second part presents the research as one of the pathways in the formation and quality of teachers, closes the article with some experiences in teacher education programs offered by the School of Education at the Universidad Industrial de Santander.